The Hidden Economy: Economic Models of Participation and Deterrence. - Basheer, Farseena (2017)
The study of the hidden economy is considered to be difficult, as those individuals who engage in the hidden economic activity do not wish to be identified. Thus, as suggested by academics, the study of hidden economy is a passion to know the unknown. The rise in the hidden economy suggests an increase in the burden on the individuals and firms imposed by the government. Tax evasion constitutes a large part of the hidden economy. A rational person will choose to evade taxes based on a rational calculus between the cost and benefit involved with hiding their income and evading taxes.